2013
DOI: 10.1111/1475-6773.12140
|View full text |Cite
|
Sign up to set email alerts
|

The Health IT Regional Extension Center Program: Evolution and Lessons for Health Care Transformation

Abstract: Objective. Assess the Regional Extension Center (REC) program's progress toward its goal of supporting over 100,000 providers in small, rural, and underserved practices to achieve meaningful use (MU) of an electronic health record (EHR). Data Sources/Study Setting. Data collected January 2010 through June 2013 via monitoring and evaluation of the 4-year REC program. Study Design. Descriptive study of 62 REC programs. Data Collection/Extraction Methods. Primary data collected from RECs were merged with nine oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 16 publications
0
51
0
Order By: Relevance
“…20 21 Information about the area-level correlates of EHR adoption and MU in the current HITECH era is beginning to emerge. One recent and noteworthy study reported substantial progress towards EHR adoption and MU among REC-enrolled PCPs based in underserved settings, assessing EHR adoption and MU patterns by practice setting, provider type, and geographic area; 22 however, this study focused on a limited set of area-level characteristics and did not assess the potential contributions of other HITECH initiatives to EHR adoption and MU.…”
Section: Introductionmentioning
confidence: 99%
“…20 21 Information about the area-level correlates of EHR adoption and MU in the current HITECH era is beginning to emerge. One recent and noteworthy study reported substantial progress towards EHR adoption and MU among REC-enrolled PCPs based in underserved settings, assessing EHR adoption and MU patterns by practice setting, provider type, and geographic area; 22 however, this study focused on a limited set of area-level characteristics and did not assess the potential contributions of other HITECH initiatives to EHR adoption and MU.…”
Section: Introductionmentioning
confidence: 99%
“…11 HITECH has also created programs to train health care providers and other staff to help implement health IT.…”
mentioning
confidence: 99%
“…These programs include the Medicare Rural Hospital Flexibility (Flex) Program, 4 the health IT Regional Extension Centers, 18 and the Workforce Development Program of the Office of the National Coordinator for Health Information Technology. 19 In addition, many federal programs offer financing or subsidies to extend access to health care through the use of such tools as teleradiology (the real-time transfer of highresolution images) and video consultations.…”
mentioning
confidence: 99%